Emerging drugs for the treatment of pruritus - Ständer, Sonja; Weisshaar, Elke; Raap, Ulrike (Expert opinion on emerging drugs, 2015)
Introduction: Chronic pruritus occurs in 13% of the general population without age limitation. There is a high unmet need here as effective treatment options are still missing.Areas covered: Clinical and experimental research during the past decade identified new mechanisms in chronic pruritus allowing the definition of a broad range of specific treatment targets for the first time. This refers specifically to inflammatory pruritic dermatoses, uremic and cholestatic pruritus. Targets identified are, for example, receptors for substance P, IL-31 and nerve growth factor. Search was made for current studies addressing these diseases and targets in the available clinical registration databases.Expert opinion: The current pharmacological development is very promising especially for patients suffering from chronic pruritus in inflammatory dermatoses, chronic kidney diseases and hepatobiliary diseases. However, there are still several pruritic diseases in which neither mediators nor specific target populations (e.g., children) nor stages of diseases, have been identified; however, it can be assumed that within the next 10 years, major changes in the possibilities of antipruritic treatment will take place.
Gesehen am 22.06.2020